Experimental Investigation of Processing Temperature Effect on Adhesive Bond Strength Between Engineering Thermoplastics in the Plastic Injection Molding Process - Özel, Ali; Soylemez, Emrecan (ASME International, 2024)
Abstract Multicomponent injection molding industry is experiencing a growth due to its ability to reduce production costs and streamline processes. However, compared to single injection, multicomponent injection molding introduces interface regions where multiple engineering polymers meet. Consequently, it is essential to comprehend and enhance the adhesive bonding strength properties of these polymers. This study investigates the adhesive bond strength of polymer–polymer multimaterial molding using two-shot bi-injection and overmolding techniques. The research also emphasizes the influence of injection molding process parameters of mold temperature and melt temperature on the adhesive bond strength of polycarbonate (PC), polycarbonate–acrylonitrile butadiene styrene (PC–ABS), acrylonitrile butadiene styrene (ABS), and styrene ethylene butadiene styrene (SEBS). Tensile strength results revealed that the bi-injection method yields the highest interface strength, approximately 10 MPa lower than the reference value for single-material hard–hard plastics. Results from overmolded samples for both injection sequences are presented, indicating that material with low melting temperature was found to be the first injected part for better adhesion strength. Empirical equations for estimating adhesion strength were derived as a function of interface temperature obtained from CAE numerical simulations and polymer glass transition temperatures. The proposed equation achieved R2 values greater than 0.96. This empirically derived equation will serve as a guide for multi-injection manufacturing processes.